Pharmacokinetics and bioequivalence of two formulations of mifepristone tablets in healthy Chinese subjects under fasting conditions: a single-center, open, randomized, single-dose, double-period, two-sequence, crossover trial - Yan, Yufeng; Zhu, Xiaoshan; Dong, Ping; Liu, Cheng; Lu, Lingqing; Zeng, Liyan; Chen, Guiying; Meng, Xianmin; Liu, Min (Frontiers in Pharmacology, 2024)
Objective: A bioequivalence (BE) study was done to evaluate the pharmacokinetics, safety, and bioequivalence of two formulations of mifepristone tablets in healthy Chinese volunteers under fasting conditions.Methods: A single-center, open, randomized, single-dose, double-period, two-sequence, crossover study in healthy subjects under fasting conditions was performed. The subjects received a single fasting dose of mifepristone (10 mg/tablet) during the first and second periods, followed by a 14-day washout period, during which frequent PK sampling occurred up to 120 hours. The pharmacokinetic parameters of mifepristone were calculated based on the plasma drug concentration-time profile. Primary endpoints were the BE of major pharmacokinetic parameters (AUC 0-t and AUC 0-∞ ) and the maximum observed serum concentration (C max ). Secondary endpoints were safety parameters.Results: Forty subjects (34 males and 6 females) were randomly assigned to treatment, of whom 39 completed the two-period study. After single administration of mifepristone tablets (test preparation vs reference preparation) under fasting conditions the GMRs of C max , AUC 0-t , AUC 0-∞ were 98.76%, 104.28% and 104.83%, respectively. The primary metabolite of mifepristone (RU42633) the GMRs of C max , AUC 0-t , AUC 0-∞ were 102.33%, 103.17% and 104.02%, respectively. The primary metabolite of mifepristone (RU42698) the GMRs of C max , AUC 0-t , AUC 0-∞ were 100.97%, 103.71% and 103.84%, respectively. All 90% confidence intervals (CIs) for the test/reference AUC ratio and Cmax ratio were within the acceptable range (80%-125%) for BE, which met the requirements of bioequivalence. No serious adverse events (AEs) occurred, and all AEs were classified as level 1 or 2.The PK parameters of mifepristone and its metabolites (RU42633 and RU42698) were measured using the geometric mean ratios (GMRs) of AUC 0-t , AUC 0-∞ and C max were similar between the test and reference drug. The two formulations of mifepristone showed good tolerability and a similar safety profile.Clinical Trial Registration: chinaDrugtrials.org.cn, identifier CTR20182413.